2009
DOI: 10.1016/j.eurpsy.2008.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Facial emotion recognition and its relationship to symptomatic, subjective, and functional outcomes in outpatients with chronic schizophrenia

Abstract: Outcome in schizophrenia is multidimensional and consists of clinical and psychosocial domains. Difficulties in affect recognition are a hallmark of schizophrenia, but there is little research investigating the consequences of this deficit on patients' psychosocial status. This cross-sectional study examined the relationship of facial affect recognition and treatment outcomes in terms of psychopathology, quality of life (QOL), and psychosocial functioning. We investigated 40 regular attendees of a specialized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 36 publications
3
27
1
9
Order By: Relevance
“…In particular, patients with the S allele showed decreased verbal learning and executive functions relative to LL homozygotes [3,9], which distinguishes patients from the general population, in which the S allele is linked with better measures of executive functions [8,62]. In the present study, the defi cit in the recognition of emotions correlated with enhancement of negative symptoms, degradation of neurocognition, and low trait anxiety, which is consistent with published data [26,32]. However, we did not see any infl uence from the 5-HTTLPR polymorphism on these features, or any signifi cant modulatory effect of these features on the association between the 5-HTTLPR polymorphism and the defect in the recognition of emotions.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In particular, patients with the S allele showed decreased verbal learning and executive functions relative to LL homozygotes [3,9], which distinguishes patients from the general population, in which the S allele is linked with better measures of executive functions [8,62]. In the present study, the defi cit in the recognition of emotions correlated with enhancement of negative symptoms, degradation of neurocognition, and low trait anxiety, which is consistent with published data [26,32]. However, we did not see any infl uence from the 5-HTTLPR polymorphism on these features, or any signifi cant modulatory effect of these features on the association between the 5-HTTLPR polymorphism and the defect in the recognition of emotions.…”
Section: Resultssupporting
confidence: 93%
“…Numbers of subjects studied in the corresponding groups are shown for each genotype (in parentheses); HWE -Hardy-Weinberg equilibrium. Effects of the 5-HTTLPR Polymorphism of the Serotonin Transporter Gene overall defi cit of perception of emotional faces in schizophrenia [26,41]. It can therefore be suggested that the effect of the 5-HTTLPR S allele on identifi cation of emotions by patients seen here is also mainly associated with the recognition of fear.…”
Section: Resultsmentioning
confidence: 86%
“…Studies on facial emotion processing, which is an aspect of social cognition, have demonstrated that schizophrenia patients have defects in interpreting the emotions and intentions of others (Marwick and Hall, 2008;Green et al, 2012). Although some studies have shown that negative symptoms are more closely associated with dysfunction in facial emotion discrimination (Mandal et al, 1999;Kohler et al, 2003;Hofer et al, 2009), the different neural correlates of facial emotional processing with respect to negative and positive symptoms have not yet been studied.…”
Section: Introductionmentioning
confidence: 97%
“…Emotion processing deficits in schizophrenia encompass multiple impairments, including emotion recognition from facial expression and prosody [15], emotion discrimination, emotion interpretation [16][17][18][19] and emotional awareness [20]. In real-world social functioning, recognizing and correctly interpreting facial emotional expressions is a crucial component for social interaction [17]. One study has shown a direct relationship between deficits in emotion recognition and the severity of negative and affective symptoms, as well as poor vocational and global functioning [18].…”
Section: Social Cognition In Schizophreniamentioning
confidence: 99%
“…These domains have been listed as: emotion processing, theory of mind, attributional bias, social perception and social knowledge. Emotion processing deficits in schizophrenia encompass multiple impairments, including emotion recognition from facial expression and prosody [15], emotion discrimination, emotion interpretation [16][17][18][19] and emotional awareness [20]. In real-world social functioning, recognizing and correctly interpreting facial emotional expressions is a crucial component for social interaction [17].…”
Section: Social Cognition In Schizophreniamentioning
confidence: 99%